(untitled) (Journal of the College of Education for Women, 2019)
The Prophet wrote many contracts and a military alliance with the Christians in order to organize their relationship with the Islam . Later on , some Christians made many changes on the contracts and the military alliance by adding some privileges , and said that the prophet gave it to them , in order to get some privileges or to be away from some dangers . The Prophet had preferred the Christians more than other Dhimes for many reasons:1.they did not resist the Islamic religion in the first stages . 2-they welcomed the Muhajrian in Habasha . 3-they were not stand against Islam openly as the Jewish had done . 4-they were neutral in the wars that had took place between the Muslims and Quraish . while the Jewish had sided Quraish in that wars . The contract and the military alliance that were related in the early Islamic sources were true . because they stayed reliable in spite of the historical criticism .while that contract and military alliance in Asyriac sources had forget for many reasons . A Great number of Christians embraced Islam ,while others remained as people of Dhima . They were free in their warship in their life and possessions . The Muslims gave them liberty of work according to Islamic sharia .